Pengaruh Substitusi Tepung Ampas Tahu Terhadap Tingkat Kekerasan Dan Daya Terima Bakso - Rahmahwati, Widi Deshinta; , Fitriana Mustikaningrum,S.Gz,M.Sc; , Eni Purwani, S.Si, M.Si (2016)
Preliminary: Meatballs is the kind of food that is shaped like a ball that is based on meat. In order meatballs with good quality and relatively affordable price, the sale price suppression need to be affordable by all circles of society. Replacing some of the meat with other ingredients that have a relatively high content of protein is one of the efforts to suppress the price of meatballs. Other additives with high protein content and is high in fiber but still has a sale value of the economy is still relatively cheap at tofu. to increase the shelf life of tofu as well as more flexibility in the use made of flour eg by means of the ease in storage and more varied in their utilization, longer shelf life and long, as well as easier storage. The meatballs tofu has a softer texture. Flour tofu has the potential to improve the texture is better because contents water and protein contained in flour tofu. Aim : The purpose of this study is to pinpoint which tah dregs flour substitution effect on the level of violence and acceptance of meatballs Research methods : This study uses a completely randomized design with 4 treatments, substitution of 0%, 5%, 10% and 15%. Hardness testing using a Lloyd's Universal Testing Machine Do-FBO.STS (Zwich / Zo.5). data analysis using SPSS 17 non-parametric analysis Descriptive Normality resumed Homogenen with Kruskal Wallis test. Result : The results showed that the highest levels of violence is by sbstitusi 15%. The test results indicate that the received power received color, aroma, flavor, texture and most preferably keseluruhanyang namely susbtitusi 0% and 5%, while the received power of color, aroma, flavor, texture and overall not preferred that the substitution of 15%. Conclusion : There is a substitution effect of oyster mushrooms against violence, acceptance of texture, flavor and overall. While the color and flavor acceptability no effect on the meatballs.